Dishes and utensils used in sacrificial rites of the Trans-Kama Udmurts (functional and symbolic meaning) - Tatiana G. Minniyakhmetova; Ranus R. Sadikov (Финно-угорский мир, 2021)
Introduction. The article considers the variety and functions of dishes and utensils used at the sacrificial rituals of Trans-Kama “pagans” Udmurts from the Republic of Bashkortostan and Perm Krai. This is the first attempt of using extensive field and archival materials for the research purposes. Materials and Methods. The material for the study represents the published and archival sources, ethnographic information collected the authors during many years of field research. The analysis of materials was carried out using a comparative-historical method. The article takes into account the theoretical approaches of the semiotic school in ethnology. Results and Discussion. In the object world of Udmurt sacrifices, a special place is occupied by dishes and utensils. Without them the ritual process involving the preparation of food and a joint meal is impossible. Various dishes (cauldrons, troughs, buckets, bowls, spoons, ladles, etc.) are used for their utilitarian purpose (cooking, storage, transportation, eating food, etc.) but inclusion in the ritual process endows them with symbolic functions. Conclusion. Dishes and utensils used at the sacrifices of the Trans-Kama Udmurts are still endowed with a high sacred status. The number, composition and methods of using ritual utensils have remained traditional but their forms, material and manufacturing method have changed. As before, in addition to being used for utilitarian purposes they are endowed with many symbolic functions.